A new energy vehicle three-electric system special high-efficiency decontamination cleaning solution
Patent Information
- Application Number
- CN202611017712.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]针对现有三电系统清洗技术需断电作业、运维效率低、易腐蚀部件、清洗后无防护层的不足,本发明提供了一种新能源车辆三电系统专用高效除污清洗液
[0020]本发明采用高绝缘性无水氟碳溶剂作为清洗分散载体,清洗液本身具备优异的绝缘性能,可直接对高压带电状态的三电系统开展作业,无需提前断电停运,同时无水氟碳溶剂常温下挥发速率快,清洗完成后无液态溶剂残留,无需额外烘干流程,有效解决了现有水基清洗技术需断电作业、烘干流程长、运维效率低,以及现有有机溶剂清洗技术挥发速率慢、残留溶剂降低部件绝缘性能的缺陷。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cleaning technology for electric drive systems, and in particular to a high-efficiency cleaning fluid specifically for the electric drive systems of new energy vehicles. Background Technology
[0002] With the continuous growth of the number of new energy vehicles, the three-electric system, as a core power component, will be subject to increased aging and insulation risks due to the accumulation of dirt such as oil, carbon powder, electrolyte crystals, and salt stains on its surface. Regular cleaning is one of the core aspects of the operation and maintenance of new energy vehicles, and the industry continues to improve its requirements for the cleaning efficiency, insulation safety, and ease of operation and maintenance of cleaning solutions.
[0003] The first type of mainstream cleaning solution for electric drive systems is water-based cleaning technology. This technology uses deionized water as a carrier, combined with surfactants, corrosion inhibitors, and chelating agents to prepare the cleaning agent. It relies on the emulsifying and penetrating effects of the surfactants to remove dirt. This method is low in raw material cost and has good cleaning effects on both polar and non-polar dirt, and is currently widely used in offline electric drive system disassembly and cleaning scenarios. However, the liquid cleaning agent in this type of solution has poor insulation, requiring a complete power outage during the cleaning process. Furthermore, it requires several hours of high-temperature drying after cleaning to restore the insulation performance of the components, resulting in a long maintenance cycle. Insufficient drying can also lead to safety hazards such as short circuits and corrosion of metal components, making it unsuitable for the rapid maintenance needs of new energy vehicles.
[0004] The second type is organic solvent cleaning technology, which mainly uses alcohol ethers and hydrocarbon solvents as core components. It relies on the principle of "like dissolves like" to dissolve oil stains and can achieve solvent evaporation without high-temperature drying, making the operation and maintenance process shorter than that of water-based solutions. However, the solvents used in this type of solution generally have high boiling points, and it takes more than 30 minutes for them to completely evaporate at room temperature. The residual solvent will significantly reduce the surface insulation performance of the three-electric system. Moreover, most organic solvents are flammable and explosive, and pose a risk of corrosion to the engineering plastics and rubber seals of the three-electric system. In addition, neither of the two existing technologies provides additional protection after cleaning. The trace impurities remaining after cleaning are harmful components and cannot improve the moisture-proof and salt spray-proof performance of the three-electric system.
[0005] In summary, existing cleaning technologies for the three electric components (battery, motor, and electronic control system) cannot simultaneously ensure insulation safety, rapid evaporation efficiency, and subsequent protective performance. They are ill-suited to the high-efficiency, safe, and long-cycle protection requirements of the current new energy vehicle operation and maintenance industry, becoming a core technological bottleneck restricting the improvement of the quality of the three electric components' operation and maintenance. Summary of the Invention
[0006] To address the shortcomings of existing cleaning technologies for the three-electric systems (battery, motor, and electronic control system), such as requiring power outages for operation, low maintenance efficiency, easy corrosion of components, and lack of a protective layer after cleaning, this invention provides a high-efficiency cleaning fluid specifically for the three-electric systems of new energy vehicles.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A high-efficiency cleaning fluid for the three-electric system (battery, motor, and electronic control system) of new energy vehicles is disclosed. The cleaning fluid is composed of anhydrous fluorocarbon solvent and soluble perfluorosilazane oligomers. The anhydrous fluorocarbon solvent serves as a dispersion carrier, used to dissolve or disperse oil, dust, and electrolyte residues adhering to the surface of the three-electric system in a liquid state. The soluble perfluorosilazane oligomers are uniformly dispersed in the anhydrous fluorocarbon solvent, with an addition amount of 0.3-5 wt% of the total mass of the cleaning fluid.
[0009] After the cleaning solution removes the dirt, the anhydrous fluorocarbon solvent evaporates rapidly at room temperature. The remaining perfluorosilazane oligomers undergo hydrolysis and condensation reactions upon contact with trace amounts of water vapor in the air, forming a silicon dioxide and silicon fluoride hybrid nanofilm with a thickness of less than 50 nm on the surface of the three-electric system. The volume resistivity of the hybrid nanofilm is greater than 10 Ω·cm. 15 Ω·cm, an insulating protective layer is formed on the surface of the three electrical systems simultaneously after cleaning.
[0010] Furthermore, the anhydrous fluorocarbon solvent is selected from any one or a combination of two or more of perfluorohexane, perfluoroheptane, and perfluorooctyl ethyl ether, with a boiling point of 40~85℃ at normal pressure and a water content of less than 10ppm.
[0011] Furthermore, the soluble perfluorosilazane oligomer is a perfluoroalkyl modified silazane oligomer with a degree of polymerization of 3 to 5, a molecular side chain fluorine content of 35 to 50 wt%, a solubility of not less than 10 g / 100 mL in anhydrous fluorocarbon solvent at room temperature, and a number average molecular weight of 400 to 2200.
[0012] Furthermore, the cleaning solution also contains 0.05~0.6wt% of a perfluoropolyether type nonionic surfactant, wherein the surfactant is hydroxyl-terminated and has a number average molecular weight of 1500~3000. After addition, the surface tension of the cleaning solution can be reduced to 15~18mN / m.
[0013] Furthermore, the volume resistivity of the cleaning fluid in its liquid state at 25°C is greater than 10 Ω·cm. 12 It has a strength of Ω·cm and can withstand a maximum live working voltage of 1000V, ensuring that it will not cause short circuits or leakage faults in the three-electric system during the cleaning process.
[0014] Furthermore, the in-situ generated silica-silicon fluoride hybrid nanofilm has a water contact angle greater than 110° and a water vapor permeability of less than 10%. -4 g / (m 2 •d) can block the penetration of water vapor, salt spray and corrosive ions, and inhibit the electromigration of metal parts.
[0015] Furthermore, the cleaning solution also contains 0.02-0.1 wt% of a methylbenzotriazole derivative copper corrosion inhibitor, which can form a monomolecular passivation layer on the surface of copper busbars and pins during the cleaning process, thus preventing oxidation and corrosion of copper components.
[0016] Furthermore, the activation energy of the hydrolysis-condensation reaction of the perfluorosilazane oligomer is 28~32kJ / mol. Under normal operating conditions of relative humidity 30~80% and temperature 10~35℃, the film can be formed in 3~10 minutes after the anhydrous fluorocarbon solvent has completely evaporated. The resulting hybrid nanofilm has an adhesion to the substrate that meets the level 0 specified in GB / T 9286.
[0017] Furthermore, the cleaning solution has a corrosion rate of less than 0.001 mm / year on copper, aluminum, nickel, ABS engineering plastics, and epoxy resin PCB substrates, and will not damage various material components of the three-electric system.
[0018] Furthermore, the cleaning fluid is compatible with various cleaning methods such as spraying, soaking, and ultrasonic-assisted cleaning. When using 0.2~0.4MPa pressure spray cleaning, the cleaning efficiency for electrolyte crystals, carbon powder, and oil stains is not less than 99%, and the single batch operation cycle does not exceed 10 minutes.
[0019] The present invention has the following beneficial effects:
[0020] This invention uses a highly insulating anhydrous fluorocarbon solvent as a cleaning and dispersion carrier. The cleaning solution itself has excellent insulating properties and can be directly applied to high-voltage energized electrical systems without prior power outages. At the same time, the anhydrous fluorocarbon solvent evaporates rapidly at room temperature, leaving no liquid solvent residue after cleaning and eliminating the need for an additional drying process. This effectively solves the problems of existing water-based cleaning technologies, which require power outages, have long drying processes, and low maintenance efficiency, as well as existing organic solvent cleaning technologies, which have slow evaporation rates and leave residual solvents that reduce the insulation performance of components.
[0021] This invention combines soluble perfluorosilazane oligomers and copper corrosion inhibitors in a cleaning solution. During the cleaning process, the corrosion inhibitors can form a monomolecular passivation layer on the surface of copper busbars, pins, and other components, preventing oxidation and corrosion of the copper components. At the same time, the residual perfluorosilazane oligomers after cleaning can generate a dense insulating hybrid nanofilm in situ on the surface of the three-electric system. This nanofilm not only has excellent insulation properties but also blocks water vapor, salt spray, and corrosive ions from penetrating the substrate and inhibits electromigration of metal components. This effectively solves the defects of existing cleaning technologies, such as easy corrosion of the three-electric system materials and no additional protective effect after cleaning.
[0022] The cleaning fluid of this invention is compatible with various conventional operation methods such as spraying, soaking, and ultrasonic-assisted cleaning. It has excellent washing efficiency for various common contaminants such as electrolyte crystals, carbon powder, and oil stains adhering to the surface of the three-electric system. The single-batch operation cycle is short, and it can be widely used in various scenarios such as production line off-line testing of new energy vehicle companies, operation and maintenance of after-sales service stations, and rapid maintenance of charging and swapping stations. It will not damage various metal and non-metal components of the three-electric system, and no additional special operation and maintenance equipment is required. It has extremely high industry promotion value. Attached Figure Description
[0023] Figure 1 This invention provides a working process for a special cleaning fluid for the three-electric system of new energy vehicles.
[0024] Figure 2 This is a dual Y-axis bar chart showing the core operational performance of different samples proposed in this invention;
[0025] Figure 3 This is a line graph showing the cleaning efficiency retention rate under accelerated aging conditions proposed in this invention.
[0026] Figure 4 This is a radar chart comparing the protective performance proposed in this invention. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] The testing methods uniformly adopt industry standard methods: volume resistivity is tested using GB / T 1410-2019 method, film thickness is tested using an ellipsometry, water contact angle is tested using a static contact angle meter, adhesion is tested using the cross-cut test method of GB / T 9286-2021, corrosion rate is tested using the immersion loss method of GB / T 16545-2025, cleaning efficiency is tested using the gravimetric method, electrical safety testing uses a 1000V DC high voltage source connected to a three-electric simulation module to monitor leakage current, accelerated aging test uses a 60℃ constant temperature chamber to store for 90 days to test performance, and ammonia residue is detected by gas chromatography to detect the concentration in a confined space.
[0029] Example 1
[0030] The cleaning solution used in this embodiment uses perfluorohexane as the dispersion carrier. Perfluorohexane has a boiling point of 56°C at normal pressure and a water content of 8 ppm. 0.3 wt% of tris(trifluoropropyl)cyclotrisilazane is added. This oligomer has a degree of polymerization of 3, a side-chain fluorine content of 35 wt%, a solubility of 12 g / 100 mL in perfluorohexane at room temperature, a number-average molecular weight of 400, and an activation energy of 28 kJ / mol for hydrolysis-condensation reaction. 0.05 wt% of a hydroxyl-terminated perfluoropolyether nonionic surfactant is added. This surfactant has a number-average molecular weight of 1500, and the surface tension of the cleaning solution after its addition is 17.2 mN / m. 0.02 wt% of a methylbenzotriazole derivative copper corrosion inhibitor is added.
[0031] The above components were stirred in a sealed container at room temperature for 15 minutes to obtain a homogeneous and transparent cleaning solution. In this example, the liquid volume resistivity of the cleaning solution at 25°C was 1.2 × 10⁻⁶. 13 The membrane has a strength of Ω·cm and can withstand a live operating voltage of 1000V. After cleaning, the perfluorohexane completely evaporates within 2 minutes. The remaining silazane oligomers undergo hydrolysis and condensation reactions in situ to form a film within 3 minutes under ambient relative humidity of 45% and temperature of 25℃. The resulting hybrid nanofilm has a thickness of 12nm and a volume resistivity of 1.5×10⁻⁶. 16 Ω·cm, water contact angle of 112°, water vapor permeability of 8.2×10 -5 g / (m 2 •d) Adhesion is grade 0; the corrosion rate of copper, aluminum, ABS engineering plastic and epoxy resin PCB substrate is 0.0006mm / year; when using 0.3MPa pressure spray cleaning, the cleaning efficiency of electrolyte crystals, toner and oil stains is 99.2%, and the single batch operation cycle is 5min.
[0032] The high-insulation fluorocarbon carrier in this embodiment solves the defect of requiring power outage operation in the prior art, the corrosion inhibitor solves the defect of easy corrosion of copper parts, and the in-situ film formation solves the defect of no protection after cleaning.
[0033] Example 2
[0034] The cleaning solution used in this embodiment uses perfluoroheptane as the dispersion carrier. Perfluoroheptane has a boiling point of 80°C at normal pressure and a water content of 7 ppm. 2.5 wt% tetra(pentafluorobutyl)cyclotetrasilazane is added. This oligomer has a degree of polymerization of 4, a side-chain fluorine content of 42 wt%, a solubility of 18 g / 100 mL in perfluoroheptane at room temperature, a number-average molecular weight of 1200, and an activation energy of 30 kJ / mol for hydrolysis-condensation reaction. 0.3 wt% hydroxyl-terminated perfluoropolyether nonionic surfactant is added. This surfactant has a number-average molecular weight of 2200, and the surface tension of the cleaning solution after its addition is 16.3 mN / m. 0.06 wt% methylbenzotriazole derivative copper corrosion inhibitor is added.
[0035] The above components were stirred in a sealed container at room temperature for 15 minutes to obtain a homogeneous and transparent cleaning solution. In this example, the liquid volume resistivity of the cleaning solution at 25°C was 2.3 × 10⁻⁶. 13 The membrane has a strength of Ω·cm and can withstand a live operating voltage of 1000V. After cleaning, the perfluoroheptane completely evaporates within 4 minutes. The remaining silazane oligomers undergo hydrolysis and condensation reactions in situ to form a film within 7 minutes under ambient relative humidity of 30% and temperature of 10℃. The resulting hybrid nanofilm has a thickness of 28nm and a volume resistivity of 2.1×10⁻⁶. 16 Ω·cm, water contact angle of 118°, water vapor permeability of 5.7×10 -5 g / (m 2 •d) Adhesion is grade 0; the corrosion rate of copper, aluminum, ABS engineering plastic and epoxy resin PCB substrate is 0.0004 mm / year; when using 0.2MPa pressure spray cleaning, the cleaning efficiency of electrolyte crystals, toner and oil stains is 99.5% and the single batch operation cycle is 7 minutes.
[0036] Example 3
[0037] The cleaning solution used in this embodiment uses perfluorooctyl ethyl ether as a dispersion carrier. Perfluorooctyl ethyl ether has a boiling point of 85°C at normal pressure and a water content of 6 ppm. 5 wt% of penta(heptafluoropentyl)cyclopentasilazane is added. This oligomer has a degree of polymerization of 5, a side-chain fluorine content of 50 wt%, a solubility of 25 g / 100 mL in perfluorooctyl ethyl ether at room temperature, a number-average molecular weight of 2200, and an activation energy of 32 kJ / mol for hydrolysis-condensation reaction. 0.6 wt% of a hydroxyl-terminated perfluoropolyether nonionic surfactant is added. This surfactant has a number-average molecular weight of 3000, and the surface tension of the cleaning solution after its addition is 15.1 mN / m. 0.1 wt% of a methylbenzotriazole derivative copper corrosion inhibitor is added.
[0038] The above components were stirred in a sealed container at room temperature for 15 minutes to obtain a homogeneous and transparent cleaning solution. In this example, the liquid volume resistivity of the cleaning solution at 25°C was 3.5 × 10⁻⁶. 12 The temperature is Ω·cm, and it can withstand a live working voltage of 1000V. After cleaning, the perfluorooctyl ethyl ether completely evaporates within 6 minutes. The residual silazane oligomers undergo hydrolysis and condensation reaction in situ to form a film under ambient relative humidity of 80% and temperature of 35℃ for 10 minutes. The resulting hybrid nanofilm has a thickness of 47nm and a volume resistivity of 1.7×10⁻⁶. 15 Ω·cm, water contact angle is 123°, water vapor permeability is 3.2×10 -5 g / (m 2 •d) Adhesion is grade 0; the corrosion rate of copper, aluminum, ABS engineering plastic and epoxy resin PCB substrate is 0.0003mm / year; when using 0.4MPa pressure spray cleaning, the cleaning efficiency of electrolyte crystals, toner and oil stains is 99.7% and the single batch operation cycle is 9min.
[0039] Example 4
[0040] The cleaning solution used in this embodiment uses a fluorocarbon solvent, a mixture of perfluorohexane and perfluoroheptane in a 1:1 mass ratio, as the dispersion carrier. The mixed solvent has a boiling point of 68°C at normal pressure and a water content of 7 ppm. 1.2 wt% tetra(pentafluorobutyl)cyclotetrasilazane is added. This oligomer has a degree of polymerization of 4, a side-chain fluorine content of 45 wt%, a solubility of 21 g / 100 mL in the mixed fluorocarbon solvent at room temperature, a number-average molecular weight of 1500, and an activation energy of 29 kJ / mol for hydrolysis-condensation reaction. 0.2 wt% hydroxyl-terminated perfluoropolyether nonionic surfactant is added. This surfactant has a number-average molecular weight of 2000, and the surface tension of the cleaning solution after its addition is 16.7 mN / m. 0.05 wt% methylbenzotriazole derivative copper corrosion inhibitor is added.
[0041] The above components were stirred in a sealed container at room temperature for 15 minutes to obtain a homogeneous and transparent cleaning solution. In this example, the liquid volume resistivity of the cleaning solution at 25°C was 1.8 × 10⁻⁶. 13 The temperature range is Ω·cm, and it can withstand a live operating voltage of 1000V. After cleaning, the mixed fluorocarbon solvent completely evaporates within 3 minutes. The residual silazane oligomers undergo hydrolysis and condensation reaction in situ to form a film under ambient relative humidity of 50% and temperature of 22℃ for 5 minutes. The resulting hybrid nanofilm has a thickness of 21nm and a volume resistivity of 1.9×10⁻⁶. 16 Ω·cm, water contact angle of 116°, water vapor permeability of 6.1×10 -5 g / (m 2•d) Adhesion is grade 0; the corrosion rate of copper, aluminum, ABS engineering plastic and epoxy resin PCB substrate is 0.0005mm / year; when using 0.3MPa pressure spray cleaning, the cleaning efficiency of electrolyte crystals, toner and oil stains is 99.4% and the single batch operation cycle is 6min.
[0042] Comparative Example 1
[0043] This comparative example uses a commercially available mainstream water-based cleaning agent for electric, electrical, and electronic systems. The components include deionized water, fatty alcohol polyoxyethylene ether, benzotriazole, and sodium citrate, with a solid content of 5wt%. The cleaning process was carried out with the power off as required by the product instructions, and the system was dried with hot air at 80℃ for 45 minutes after cleaning.
[0044] The volume resistivity of the cleaning solution in this comparative example at 25°C is 1.2 × 10⁻⁶. 6 The leakage current reached 12.6 mA during forced live-line operation, directly triggering short-circuit protection; after cleaning, there was no in-situ film formation effect, the water contact angle on the component surface was 52°, and the water vapor permeability was 1.3 × 10⁻⁶. -2 g / (m 2 •d) The corrosion rate of copper parts is 0.021 mm / year; the cleaning efficiency is 92.3% and the single batch operation cycle is 62 min.
[0045] Reaction molecular formula and explanation
[0046] The hydrolysis-condensation reaction formula for perfluorosilazane oligomers is as follows:
[0047] [R f Si(NH)] n +nH2O→[R f Si(OH)] n +nNH3
[0048] 2[R f Si(OH)] n →[R f Si-O-SiR f ] n +nH2O
[0049] R f The radical is a perfluoroalkyl group, and n represents the degree of polymerization 3-5. A subsequent condensation reaction occurs between the hydroxyl groups to remove water molecules, generating a hybrid network structure of silicon dioxide and silicon fluoride with -Si-O-Si- as the main chain and perfluoroalkyl groups branched on the sides. This reaction has an activation energy of 28-32 kJ / mol, can proceed rapidly at room temperature, and releases extremely low concentrations of ammonia gas, posing no harm to components of the electrical system or maintenance personnel. Simultaneously, the resulting hybrid film possesses excellent insulation and protective properties, addressing the deficiency of existing technologies that lack a protective layer after cleaning.
[0050] Test data table and explanation
[0051] Table 1 Core performance test results
[0052] Example 1 <![CDATA[1.2×10 13 ]]> 1000 3 12 <![CDATA[1.5×10 16 ]]> 112 0.0006 99.2 5 Example 2 <![CDATA[2.3×10 13 ]]> 1000 7 28 <![CDATA[2.1×10 16 ]]> 118 0.0004 99.5 7 Example 3 <![CDATA[3.5×10 12 ]]> 1000 10 47 <![CDATA[1.7×10 15 ]]> 123 0.0003 99.7 9 Example 4 <![CDATA[1.8×10 13 ]]> 1000 5 21 <![CDATA[1.9×10 16 ]]> 116 0.0005 99.4 6 Comparative Example 1 <![CDATA[1.2×10 6 ]]> <220 none none none 52 0.021 92.3 62
[0053] The data in this table shows that the cleaning solutions in all embodiments can withstand a 1000V live working voltage, with no risk of leakage or short circuit. After cleaning, a highly insulating protective film can be quickly formed, and the corrosion rate on copper components is much lower than that of the comparative example. The cleaning efficiency and operation cycle are better than those of the comparative example, solving the core defects of the existing technology, such as the need for power-off operation, low maintenance efficiency, easy corrosion of components, and lack of protective layer.
[0054] Table 2. Stability and safety test results
[0055] Example 1 Transparent and uniform 0 98.7 0.018 0.07 Example 2 Transparent and uniform 0 99.1 0.022 0.05 Example 3 Transparent and uniform 0 98.3 0.027 0.09 Example 4 Transparent and uniform 0 98.9 0.021 0.06 Comparative Example 1 Layered turbidity 12.3 81.2 0 12.6
[0056] The data in this table show that the cleaning solutions in each embodiment exhibit excellent storage stability, with no risk of gel failure after 90 days of accelerated aging, a cleaning efficiency retention rate close to 100%, and ammonia concentration released during film formation far below the national standard of 20 mg / m³. 3 Occupational exposure limits, no corrosive gas hazards, and leakage current during live-line work are far below the safety threshold of 1mA, which solves the defects of poor storage stability and potential safety hazards in existing technologies.
[0057] refer to Figure 2 This figure visually illustrates the differences in core operation and maintenance performance between the embodiments of this invention and existing mainstream water-based cleaning agents. The single-batch operation cycle of all embodiments does not exceed 9 minutes, less than 1 / 7 of the comparative example. No power outage or subsequent drying process is required, and the cleaning efficiency is consistently above 99%, exceeding the comparative example by more than 7 percentage points. This directly demonstrates the effectiveness of this invention in solving the shortcomings of low operation and maintenance efficiency and the need for long-term vehicle downtime in existing technologies. It indicates that this technical solution has excellent performance stability and can adapt to the standardized operation requirements of different operation and maintenance scenarios.
[0058] refer to Figure 3 This figure simulates the results of an accelerated aging test at 60°C for 18 months at room temperature, showing the differences in long-term storage stability among the three cleaning methods. After 90 days of aging, the cleaning efficiency retention rate of the embodiment group of this invention remained close to 99%, with no gelation, stratification, or turbidity, far exceeding the 81.2% of the comparative example and the 89.2% of commercially available organic solvent cleaning agents. This indicates that the anhydrous fluorocarbon solvent of this invention has excellent compatibility with perfluorosilazane oligomers, and will not undergo hydrolysis, polymerization, or other failure reactions during storage. It solves the defects of existing water-based cleaning agents, such as easy stratification and easy degradation of active ingredients, and can meet the application requirements of long-term storage and cross-regional transportation.
[0059] refer to Figure 4This figure shows the performance differences of three cleaning schemes in the long-term protection dimension of the three-electric system. The best group of the embodiment performs significantly better than the two existing technologies in all five dimensions. In particular, the advantages of high insulation, hydrophobicity and salt spray resistance are prominent. This shows that the hybrid nanofilm generated in situ by the present invention can achieve multiple effects of insulation protection, water vapor barrier and corrosion protection at the same time. It solves the defects of existing technologies that have no protective layer after cleaning and are easy to corrode the metal and non-metal parts of the three-electric system. It can effectively extend the operation and maintenance interval of the three-electric system and reduce the long-term operation and maintenance cost.
[0060] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high-efficiency cleaning fluid specifically for the three-electric system of new energy vehicles, characterized in that, The cleaning solution is composed of anhydrous fluorocarbon solvent and soluble perfluorosilazane oligomers; the anhydrous fluorocarbon solvent serves as a dispersion carrier, used to dissolve or disperse oil, dust, and electrolyte residues adhering to the surface of the three-electric system in a liquid state; the soluble perfluorosilazane oligomers are uniformly dispersed in the anhydrous fluorocarbon solvent, with an addition amount of 0.3~5 wt% of the total mass of the cleaning solution. After the cleaning solution removes the dirt, the anhydrous fluorocarbon solvent evaporates rapidly at room temperature. The remaining perfluorosilazane oligomers undergo hydrolysis and condensation reactions upon contact with trace amounts of water vapor in the air, forming a silicon dioxide and silicon fluoride hybrid nanofilm with a thickness of less than 50 nm on the surface of the three-electric system. The volume resistivity of the hybrid nanofilm is greater than 10 Ω·cm. 15 Ω·cm, an insulating protective layer is formed on the surface of the three electrical systems simultaneously after cleaning.
2. The high-efficiency cleaning fluid for the three-electric system of new energy vehicles according to claim 1, characterized in that, The anhydrous fluorocarbon solvent is selected from any one or a combination of two or more of perfluorohexane, perfluoroheptane, and perfluorooctyl ethyl ether, with a boiling point of 40~85℃ at normal pressure and a water content of less than 10ppm.
3. The high-efficiency cleaning fluid for the three-electric system of new energy vehicles according to claim 1, characterized in that, The soluble perfluorosilazane oligomer is a perfluoroalkyl modified silazane oligomer with a degree of polymerization of 3 to 5, a molecular side chain fluorine content of 35 to 50 wt%, a solubility of not less than 10 g / 100 mL in anhydrous fluorocarbon solvent at room temperature, and a number average molecular weight of 400 to 2200.
4. The high-efficiency cleaning fluid for the three-electric system of new energy vehicles according to claim 1, characterized in that, The cleaning solution also contains 0.05-0.6 wt% of a perfluoropolyether nonionic surfactant, wherein the surfactant is hydroxyl-terminated and has a number average molecular weight of 1500-3000.
5. The high-efficiency cleaning fluid for the three-electric system of new energy vehicles according to claim 1, characterized in that, The cleaning fluid has a volume resistivity greater than 10 Ω·cm in its liquid state at 25°C. 12 Ω·cm.
6. The high-efficiency cleaning fluid for the three-electric system of new energy vehicles according to claim 1, characterized in that, The in-situ generated silica-silicon fluoride hybrid nanofilm has a water contact angle greater than 110° and a water vapor permeability of less than 10%. -4 g / (m 2 ·d).
7. The high-efficiency cleaning fluid for the three-electric system of new energy vehicles according to claim 1, characterized in that, The cleaning solution also contains 0.02-0.1 wt% of a methylbenzotriazole derivative copper corrosion inhibitor.
8. The high-efficiency cleaning fluid for the three-electric system of new energy vehicles according to claim 1, characterized in that, The activation energy of the hydrolysis-condensation reaction of the perfluorosilazane oligomer is 28~32kJ / mol. Under normal operating conditions of relative humidity 30~80% and temperature 10~35℃, the film can be formed in 3~10 minutes after the anhydrous fluorocarbon solvent has completely evaporated. The resulting hybrid nanofilm has an adhesion to the substrate that meets the level 0 specified in GB / T 9286.
9. The high-efficiency cleaning fluid for the three-electric system of new energy vehicles according to claim 1, characterized in that, The cleaning solution exhibits a corrosion rate of less than 0.001 mm / year on copper, aluminum, nickel, ABS engineering plastics, and epoxy resin PCB substrates.
10. The high-efficiency cleaning fluid for the three-electric system of new energy vehicles according to claim 1, characterized in that, The cleaning fluid is suitable for various cleaning methods, including spraying, soaking, and ultrasonic-assisted cleaning. When using 0.2~0.4MPa pressure spray cleaning, the cleaning efficiency for electrolyte crystals, carbon powder, and oil stains is not less than 99%, and the single batch operation cycle does not exceed 10 minutes.